Interactive Sections of an Internet-Based Intervention Increase Empowerment of Chronic Back Pain Patients: Randomized Controlled Trial - Riva, Silvia; Camerini, Anne-Linda; Allam, Ahmed; Schulz, Peter J (JMIR Publications, 2014)
BackgroundChronic back pain (CBP) represents a significant public health problem. As one of the most common causes of disability and sick leave, there is a need to develop cost-effective ways, such as Internet-based interventions, to help empower patients to manage their disease. Research has provided evidence for the effectiveness of Internet-based interventions in many fields, but it has paid little attention to the reasons why they are effective. ObjectiveThis study aims to assess the impact of interactive sections of an Internet-based self-management intervention on patient empowerment, their management of the disease, and, ultimately, health outcomes. MethodsA total of 51 patients were recruited through their health care providers and randomly assigned to either an experimental group with full access to the Internet-based intervention or a control group that was denied access to the interactive sections and knew nothing thereof. The intervention took 8 weeks. A baseline, a mid-term after 4 weeks, and a final assessment after 8 weeks measured patient empowerment, physical exercise, medication misuse, and pain burden. ResultsAll patients completed the study. Overall, the intervention had a moderate effect (F1.52=2.83, P=.03, η2=0.30, d=0.55). Compared to the control group, the availability of interactive sections significantly increased patient empowerment (midterm assessment: mean difference=+1.2, P=.03, d=0.63; final assessment: mean difference=+0.8, P=.09, d=0.44) and reduced medication misuse (midterm assessment: mean difference=−1.5, P=.04, d=0.28; final assessment: mean difference=−1.6, P=.03, d=−0.55) in the intervention group. Both the frequency of physical exercise and pain burden decreased, but to equal measures in both groups. ConclusionsResults suggest that interactive sections as part of Internet-based interventions can positively alter patients' feelings of empowerment and help prevent medication misuse. Detrimental effects were not observed. Trial RegistrationClinicalTrials.gov: NCT02114788; http://www.clinicaltrials.gov/ct2/show/NCT02114788 (Archived by WebCite at http://www.webcitation.org/6ROXYVoPR).